KOAD implemented automatic ICU signalling and error minimization - Shemonti, Nazifa Mubashshera; Chakraborty, Arnoba; Ibnat, Aniqa Afra (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.